Evaluation Of Patient Satisfaction Of Bruxzir Zirconia Complete Coverage Crowns With Feather Edge Versus Deep Chamfer Margin Design. (Randomised Controlled Trial) (Journal of Pharmaceutical Negative Results, 2023)
Background: patient satisfaction is one of the main concerns during the construction full coverage restoration. success of the crown depends on many aspects such as color, anatomic form, no pain or gingival inflammation, restoration integrity and finally retention of the restoration.Aim: To assess the effect of margin design (feather edge versus deep chamfer) of Bruxzir zirconia ceramic crowns on patient’s satisfaction.Methodology: A total of twenty patients (age range 19- 50 years old) with premolar teeth requiring full coverage restorations, were randomly allocated into two groups (n= 10) according to the margin design tested; Group DC (control): deep chamfer and Group FE (intervention): feather edge. All crowns were constructed from monolithic Bruxzir zirconia. After crowns cementation, patient satisfaction was assessed using a customized questionnaire after 6 months & 1-year using Likert scale. The obtained data were tested for normality and expressed as frequency and percentages. Further Statistical analysis was performed using Chi square test.Results: Patient satisfaction was higher in FE group compared to DC group regarding pain and gingival health questions, with statistically insignificant difference between both groups (p<.0.05) after 6 months and 1 year follow up.Conclusions: Margin geometry (feather edge of deep chamfer) of all ceramic Bruxzir crowns achieved high level of patient satisfaction without affecting the patient satisfaction along one year follow up period.